2016
DOI: 10.1159/000446434
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Determination of the Greulich-Pyle Bone Age as an Alternative Approach for Chinese Children with Discordant Bone Age

Abstract: Background: Automated bone age (BA) rating using BoneXpert is being adopted worldwide. This study investigated whether manual matching of hand radiographs could be replaced by BoneXpert for BA ratings of Chinese children with delayed or advanced BA. Methods: 482 left-hand radiographs from 482 children (aged 2-16 years) with discordant BA were evaluated by BoneXpert and manually by 4 radiology residents using the Greulich and Pyle atlas. Radiographs whose BoneXpert BA deviated by >1 year from manual assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It can occur at any stage of the child's growth. Idiopathic dwarfism: idiopathic dwarfism [ 10 ] is a temporarily unspecified cause of dwarfism and is one of the most common types of dwarfism. This type of dwarfism is usually due to the mother's own disease at the time of pregnancy, such as maternal gestational hypertension and maternal smoking and drug use, which can cause intrauterine growth retardation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It can occur at any stage of the child's growth. Idiopathic dwarfism: idiopathic dwarfism [ 10 ] is a temporarily unspecified cause of dwarfism and is one of the most common types of dwarfism. This type of dwarfism is usually due to the mother's own disease at the time of pregnancy, such as maternal gestational hypertension and maternal smoking and drug use, which can cause intrauterine growth retardation.…”
Section: Related Workmentioning
confidence: 99%
“…Idiopathic dwarfism: idiopathic dwarfism [ 10 ] is a temporarily unspecified cause of dwarfism and is one of the most common types of dwarfism.…”
Section: Related Workmentioning
confidence: 99%
“…Rather, we aimed to correlate G&P and TW3 against known CA of a healthy modern population and found that G&P remains reliable (consistent with the results of a recent systematic review) [48]. The question of accuracy of BoneXpert has already been answered in primary research studies [4951], whereas as far as we are aware, the assessment of the applicability of the standards themselves has not been previously performed using objective software and only a few have considered socioeconomic status [12, 14, 52–54]. Contrary to our results, these studies have shown delayed bone age in children of low socioeconomic status—it is possible that the degree of deprivation in the children from these studies was greater than in ours.…”
Section: Discussionmentioning
confidence: 84%
“…Several methods have been used to assess radiological bone age over time, the main problem is the inter-and intra-rater reliability (7)(8)(9)(10)(11)(12)(13)(14) . The most commonly used methods are the Greulich and Pyle atlas (GP) and the Tanner-Whitehouse method (TW), both performed through the assessment of left hand x-rays.…”
Section: Introductionmentioning
confidence: 99%